2011
DOI: 10.1148/radiol.11101106
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Pneumatically Actuated MR-compatible Robot for Transrectal Prostate Biopsy Guidance

Abstract: It is feasible to perform transrectal prostate biopsy with real-time 3-T MR imaging guidance with the aid of a remote-controlled, pneumatically actuated MR-compatible robotic device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 32 publications
1
52
0
Order By: Relevance
“…[16][17][18][19] Series describing MRI-guided biopsy techniques showed detection rates varying from 15% to 59% with a number of biopsy cores between 3 and 10. [20][21][22][23][24][25][26][27] This is again highlighting the importance of patient selection in the comparison of these techniques, as noted by Singh et al 25 Our study evaluated the results of targeted biopsies, but beforehand offered an evaluation of prostate MRI. Biopsy results according to PI-RADS scores reflected the reliability of MRI interpretation and the reproducibility of the score.…”
Section: Commentmentioning
confidence: 58%
“…[16][17][18][19] Series describing MRI-guided biopsy techniques showed detection rates varying from 15% to 59% with a number of biopsy cores between 3 and 10. [20][21][22][23][24][25][26][27] This is again highlighting the importance of patient selection in the comparison of these techniques, as noted by Singh et al 25 Our study evaluated the results of targeted biopsies, but beforehand offered an evaluation of prostate MRI. Biopsy results according to PI-RADS scores reflected the reliability of MRI interpretation and the reproducibility of the score.…”
Section: Commentmentioning
confidence: 58%
“…Other future steps will be to investigate the long-term follow-up of the treated patients, to optimize the workflow, and to perform MR imaging-guided cryoablation in combination with an MR imaging-compatible robot (28). Workflow optimization and robotic needle placement could further decrease the procedure and treatment times.…”
Section: Discussionmentioning
confidence: 99%
“…There has been much discussion on how to improve the accuracy of prostate needle sampling [12,26]. New techniques such as MRI guidance, image fusion and robotic assistance are being tested to help minimize faulty needle placement [27][28][29]. It has also been suggested that, to further improve the accuracy of prostate biopsies, biopsy cores could be stained at one end to show the apical-basal orientation [30].…”
Section: Discussionmentioning
confidence: 99%